Decentralized online social network primitives. - Rajesh Sharma. (2013)
Centralized online Social networks such as Facebook are highly popular [1]. Despite their success, a prominent concern about such centralized systems is privacy [2] [3] from the service providers themselves. In order to address these shortcomings, researchers have proposed decentralized architectures for social networks. Examples of such Decentralized Online Social Networks (DOSNs) include Peerson [4], Vis-a-Vis [5] and Safebook [6].